Psychosocial predictors of weight loss by race and sex. Issue 5 (21st October 2015) - Jerome, G. J.; Myers, V. H.; Young, D. R.; Matthews‐Ewald, M. R.; Coughlin, J. W.; Wingo, B. C.; Ard, J. D.; Champagne, C. M.; Funk, K. L.; Stevens, V. J.; Brantley, P. J.
Summary: This paper examined the psychosocial predictors of weight loss among race and sex subgroups. Analyses included overweight and obese participants from the PREMIER study, a previously published randomized trial that examined the effects of two multi‐component lifestyle interventions on blood pressure among pre‐hypertensive and stage 1 hypertensive adults. Both intervention conditions received behavioural recommendations for weight loss and group sessions. Weight and psychosocial measures of self‐efficacy and social support for diet and exercise were assessed at baseline and at 6 months. There were 157 African–American (AA) women, 46 AA men, 203 non‐AA women and 182 non‐AA men with an average age of 50 years and average body mass index of 34 at baseline. Multiple predictor regression models were performed individually by race and sex subgroup. Among AA women, increases in diet self‐efficacy were associated with weight loss. Among AA men, increases in diet‐related social support and self‐efficacy, along with increases in family support to exercise, were associated with weight loss (all P s <0.05). Among non‐AA women, increases in friends' support to exercise and exercise‐related self‐efficacy were associated with weight loss, and among non‐AA men only increases in diet self‐efficacy were associated with weight loss (all P s <0.05). These results emphasize the need for targeted interventions based on race and sex to optimize the impact of lifestyle‐based weight loss programmes.